EFEKTIVITAS MEDIA TANGRAM TERHADAP MINAT BELAJAR MATEMATIKA BANGUN DATAR PADA SISWA KELAS II SD N BAJING 2 - Nurhayati; Budiharti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study began with observations indicating that students’ interest in learning mathematics was relatively low, particularly in the topic of plane geometry. This low level of interest is presumed to be related to the use of conventional teaching methods that tend to be teacher-centered, resulting in limited student engagement during the learning process. Such conditions highlight the need for innovative instructional approaches that can foster students’ interest and active participation. One potential solution is the use of concrete learning media based on tangram. The purpose of this study was to determine the effectiveness of using tangram-based concrete media in improving the learning interest of second-grade students at SD Negeri Bajing 2 Kroya. The research employed a quasi-experimental method with a nonequivalent control group design. The participants were divided into two groups: an experimental group consisting of 19 students and a control group consisting of 17 students. The experimental group received instruction using tangram-based concrete media, while the control group was taught using conventional methods. Data were collected through a learning interest questionnaire administered before and after the intervention. The collected data were analyzed using the Independent Samples t-test. The results showed that the average learning interest score in the experimental group reached 80.64%, while the control group achieved 69.41%. The significance value obtained was 0.000 (<0.05), leading to the rejection of the null hypothesis. Therefore, it can be concluded that the use of tangram-based concrete media is effective in enhancing students’ learning interest compared to conventional teaching methods.